The Effects of Decimalization on Return Volatility Components, Serial Correlation and Trading Costs - HE, Yan (Institutional Knowledge at Singapore Management University, 2005)
We examine the composition of return volatility, serial correlation, and trading costs before and after decimalization on the New York Stock Exchange. We decompose the variance of price changes into components associated with public news, rounding errors, and market-making frictions. We find that when stocks move from a fractional to a decimal trading system, the variance components due to market-making frictions and rounding errors decline significantly, whereas the component due to public news remains unchanged. The serial correlation of price changes weakens substantially after decimalization. The uninformed component of bid-ask spreads decreases significantly whereas the informed component has no significant change.